Comparative Analysis of Indonesian Presidents’ Identities in Wayang during the Reformasi Era - Stanley Elias (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2020)
This study comparatively analyses the allusion and analogies of Indonesian Presidents’ by wayang characters and stories. It particularly interrogates how wayang characters and lakon allude and mediate the personal and political identities of Indonesian presidents in the Reformasi era. The study focuses on the portrayal of President Susilo Bambang Yudhoyono and Jokowi during Reformasi era. The study is a qualitative research and deploying Textual and Critical Discourse Analysis approaches. These are to examine how language in the selected wayang kulit and wayang golek stories, as a form of social and cultural practice, constructs the personal and political identities of the presidents. Central to the analysis, Susilo Bambang Yudhoyono is in most cases alluded as Semar, and his association with selected lakon significantly inform on the political and personal identities among Indonesians and the International community. On the other hand, Jokowi is alluded to as Petruk but presenting contradicting allusions and analogies in Indonesian politics. Generally, findings suggest that the portrayal of Indonesian presidents’ identities by wayang characters and in the lakon is never fixed. The change of political atmosphere and failure to meet peoples’ expectations culminate in changes on the portrayal of political and personal identities of presidents.